Incidence and Patterns of Mandibular Fractures: A Retrospective Institutional Study - RAJASHRI; KUMAR, M P SANTHOSH; SELVARASU, KATHIRAVAN (The journal of contemporary issues in business and government, 2020)
The aim of this study was to assess patterns of mandibular fractures and its relationship with etiology. This descriptive, cross-sectional study analyzed all patients aged above 8 years who had been clinically or radiographically diagnosed with mandibular fractures from June, 2019 to March, 2020. Patients with pathological fractures or blast injuries were excluded. Data were analyzed using IBM SPSS Statistics for Windows, Version 20.0 (IBM Corp., Armonk, NY) and results obtained. Among 46 patients involved in mandibular fractures 41 were men (89.1%) and 5 were women (10.9%), and the majority of trauma patients (34.8%) were aged 21-30 years. The most frequent cause of mandibular fracture was road traffic accidents (RTA) mostly due to drunken driving (RTAs; 59.4%), followed by falls (18.8%). In patients with unilateral fractures, the most frequent site was the angle (23.9%), followed by the parasymphysis (15.2%). In patients with bilateral fractures, the most common sites were the dentoalveolar area (13%). All these results were statistically significant. p<0.05. On comparing the association between type of mandibular fractures and the other associated fractures, the results were statistically not significant. p>0.05. More mandibular fractures were present in men than in women mostly among the young adults. The most common etiological factor for mandibular fractures was road traffic accidents due to drunken driving, followed by falls. The most frequently fractured site was the angle of mandible followed by parasymphysis. The incidence of RTAs and resultant fractures may be reduced by strict prohibition of drunken driving, mandatory wearing of helmets, maintaining speed limits, and obeying proper traffic rules.